Numerical Study Of Viscous Effects On Acoustic Waves - Mohd. Ghazali, Normah (Penerbit UTM Press, 2002)
A two-dimensional numerical simulation of acoustic waves in a closed rectangular acoustic chamber is completed. Numerical computations are performed by solving the two-dimensional, unsteady, viscous, non-linear Navier-Stokes system of equations. Finite difference methodology was used accurate to second order both in time and space. No-slip, no through flow and zero heat flux are set boundary conditions. Acoustic waves are generated by a vibrating membrane or piston on one wall. Computations are completed for variation in viscosity of the fluid. Results of the temperature profiles seem to agree with analytical solutions for a standing wave in an enclosure and those obtained experimentally with low perturbation to mean pressure ratio. Temperature nodes and anti-nodes each was found to occur near walls and midway through the chamber respectively, results associated with a half wavelength standing wave.